2013
DOI: 10.1051/0004-6361/201220865
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit alignment in the very low mass binary regime

Abstract: Studies of solar-type binaries have found coplanarity between the equatorial and orbital planes of systems with <40 AU separation. By comparison, the alignment of the equatorial and orbital axes in the substellar regime, and the associated implications for formation theory, are relatively poorly constrained. Here we present the discovery of the rotation period of 3.32 ± 0.15 h from 2MASS J0746+20A -the primary component of a tight (2.7 AU) ultracool dwarf binary system (L0+L1.5). The newly discovered period, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 64 publications
(103 reference statements)
2
40
0
Order By: Relevance
“…Forbrich et al (2016) further use their astrometric monitoring to rule out Jupiter-mass companions in the NLTT 33370 AB system in a wide variety of orbits; however, a smaller rocky planet may be sufficient to provide the conditions to drive an auroral engine. Similarly, the L0.5+L1.5 binary 2MASSI J0746425+200032 with separation 2.9 au (237.3 mas on the sky; Konopacky et al 2010) shows periodic radio and Hα emission at the same 2.072 hr period, attributable to the secondary, while the primary has a confirmed photometric period of 3.32 hr (Berger et al 2009;Harding et al 2013b). Like NLTT 33370, the components of 2MASS J0746+2000 have similar physical properties but very different magnetic emissions.…”
Section: The Possible Role Of Planetary Companionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Forbrich et al (2016) further use their astrometric monitoring to rule out Jupiter-mass companions in the NLTT 33370 AB system in a wide variety of orbits; however, a smaller rocky planet may be sufficient to provide the conditions to drive an auroral engine. Similarly, the L0.5+L1.5 binary 2MASSI J0746425+200032 with separation 2.9 au (237.3 mas on the sky; Konopacky et al 2010) shows periodic radio and Hα emission at the same 2.072 hr period, attributable to the secondary, while the primary has a confirmed photometric period of 3.32 hr (Berger et al 2009;Harding et al 2013b). Like NLTT 33370, the components of 2MASS J0746+2000 have similar physical properties but very different magnetic emissions.…”
Section: The Possible Role Of Planetary Companionsmentioning
confidence: 97%
“…h Period precision is quoted by Wolszczan & Route (2014) as 7ms. i Physical properties combine dynamical measurements by Konopacky et al (2010) and evolutionary models (Harding et al 2013b). The period of the primary is determined from photometric monitoring, which distinguishes the radio emission to be from the secondary (Harding et al 2013b).…”
Section: Brown Dwarf Auroraementioning
confidence: 99%
“…The flaring L1.5 brown dwarf of the binary 2MASS J07464256+2000321 system (Berger et al 2009;Harding et al 2013) which has been observed over 7 years, appears to have undergone one complete activity cycle, featuring two polarity reversals. From data collected in 2007 Jan (Antonova et al 2008) and 2008 Feb (Berger et al 2009), the radio emission is observed to flare repeatedly, but the helicity of the polarization is always highly LCP.…”
Section: Magnetismmentioning
confidence: 99%
“…If the possible source detected in our NIRC2 images is the companion, an inertial orbit measurement should be achieveable in 2-5 yr by combining astrometric and radial velocity monitoring. Note that a robust detection of photometric variability would allow us to measure the rotational axis inclination of WISE J0720-0846A and assess spin-orbit alignment in this system, a critical test of binary formation that has only been examined in one VLM binary to date (Harding et al 2013).…”
Section: Physical Properties Of the Wise J0720-0846 Systemmentioning
confidence: 99%